CONSTATATIVE STUDY ON THE LEVEL OF PHYSICAL TRAINING OF U19 JUNIOR FOOTBALLERS IN ROMANIA - Gabriel SIMION (Editura Universitatii Transilvania din Brasov, 2020)
In this research we aimed to assess the level of general and specific physical preparation of U19 (under 19 years) juniors' football game ascertaining experiment was undertaken. To this end, we organized and ran from March to September 2018 preliminary experiment. Evaluation of physical training for juniors U19 was as physical tests established by the Romanian Football Federation, applied junior national teams. Thus, these physical tests were applied to a number of 196 athletes, juniors 17-18 years in Romania and the two teams expected ingredients for inclusion in pedagogical experiment basis. Results and discussion arising from this study are included in this paper